A unique scrotal extratesticular epidermod cyst attached to the seminal vesicles - Sağlam, Hasan Salih; Kumsar, Şükrü; Köse, Osman; Adsan, Oztuğ (Canadian Urological Association Journal, 2013)
A 46-year old man was admitted with a scrotal long standing painless mass. The work up included physical examination, alpha- fetoprotein (αFP) and beta-human chorionic gonadotropin (β-hCG) analyses, scrotal ultrasound (US), magnetic resonance imaging (MRI) and urethrocystoscopy. The patient underwent surgery. Surgical exploration revealed a separate mass between the testes extending superiorly with a thin stalk. It was dissected easily to the anterior aspect of the seminal vesicles and removed from the junction to the seminal vesicles. Pathology reported an epidermoid cyst. To our knowledge this is the first case of a scrotal extratesticular epidermoid cyst attached to the seminal vesicles. Epidermoid cysts can be seen anywhere in the midline from the cranium to the anus. Embriologically abnormal closure of neural groove or epithelial fusion lines is one of the theories that seem more probable. Genital epidermoid cysts are rare, painless and usually located in the testes. Up to date less than 10 case reports of extratesticular epidermoid cysts have been published. For those cases malignancy may not be ruled out, so the surgical removal was advocated.